2008
DOI: 10.1177/112067210801800103
|View full text |Cite
|
Sign up to set email alerts
|

Tear Concentrations of Azithromycin following Topical Administration of a Single Dose of Azithromycin 0.5%, 1.0%, and 1.5% Eyedrops (T1225) in Healthy Volunteers

Abstract: Once daily instillation of T1225 1.0% and 1.5% was shown to reach an AUIC markedly above the required threshold for an antibacterial activity against Gram-positive bacteria (25-35). These results suggest that a BID instillation is more likely to ensure antimicrobial activity against Gram-negative bacteria (threshold >100).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 36 publications
0
23
1
Order By: Relevance
“…The besifl oxacin levels in tears measured in this study were generally higher than the levels reported following a single topical ocular instillation of ciprofl oxacin (0.3%), 24 ofl oxacin (0.3%), 24 norfl oxacin (0.3%), 24 levofl oxacin (0.5%), 12 or azithromycin (1%) 13 (Fig. 9).…”
Section: Systemic Pharmacokineticscontrasting
confidence: 48%
See 2 more Smart Citations
“…The besifl oxacin levels in tears measured in this study were generally higher than the levels reported following a single topical ocular instillation of ciprofl oxacin (0.3%), 24 ofl oxacin (0.3%), 24 norfl oxacin (0.3%), 24 levofl oxacin (0.5%), 12 or azithromycin (1%) 13 (Fig. 9).…”
Section: Systemic Pharmacokineticscontrasting
confidence: 48%
“…Data for ciprofl oxacin, ofl oxacin, and norfl oxacin are from Akkan and colleagues 24 ; data for levofl oxacin are from Raizman and colleagues 12 ; data for azithromycin are from Chiambaretta and colleagues. 13 …”
Section: Figmentioning
confidence: 97%
See 1 more Smart Citation
“…This could explain why even bacteria resistant to plasma concentrations of azithromycin are susceptible to azithromycin eye drop treatment (which has an antibiotic concentration several times the minimum inhibitory concentration for bacteria usually defined as resistant)27. The pharmacokinetic properties of azithromycin justify the short treatment duration of only one drop twice-daily for 3 days for a rapid antibacterial action29. The present study has confirmed that this treatment regimen, already established in adults, is also effective in the paediatric population, including children younger than 24 months old.…”
Section: Discussionmentioning
confidence: 99%
“…The drug is currently available as eyedrops at a concentration of 1.5 % as Azyter ® (Laboratoires Theá, Clermont-Ferrand, France) and 1.0 % concentration as Azasite (Inspire Pharmaceuticals Inc, NC, USA). The tear concentration of topical azithromycin was studied following topical administration of a single dose of azithromycin 1.0 and 1.5 % in healthy volunteers [ 32 ]. This study was a prospective, randomized double-masked study.…”
Section: Antibiotics That Inhibit Protein Synthesismentioning
confidence: 99%